Effectiveness of Antibiotic paste in necrosed primary teeth with periapical abscess and fistula - Quintana del Solar, Carmen Inocencia (2012)
The aim of this study was to evaluate the effectiveness of one paste triantibiotica as a treatment in one piece with periapical abcess and fistula. We report a patient of for years old, who had presented a necrotic primary molar with abcess and fistula, we decided to make the pulpectomy using antibiotic paste formed by ciprofloxacin, metronidazole, minocycline and propyleneglycol to inhibit microorganisms present and preserve the piece. After removal of enteric coating, these drugs were pulverized using terile mortar and pestle, and then one increment of each powdered drug was mixed with propylene glycol to form an ointment just before use. The result of this paste was effective showing clinical and radiographic improvements.